Chemigation laws - Skoglund, L. G., author; McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2015)
Colorado Chemigation Act, State of Colorado Title 35 Article 11. The Colorado Chemigation Act provides for regulation of chemigation by setting standards for equipment and establishing procedures for inspection.
CEPEP 10/01, updated 5/15.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Agricultural chemicals -- Foliar application -- Colorado; Chemigation -- Colorado; Pesticides -- Colorado